Tagalog slang dictionary - Zorc, R. David; San Miguel, Rachel; Sarra, Annabelle M.; Afable, Patricia O. (De La Salle University Press, 1993)
Recordings of such neologism (new word or meaning) that were counter-checked with the standard Tagalog-English dictionary to cull out "gay language". It provides definitions for words that cannot be found in already existing resources. Includes curses and sexually explicit terms.